Relevansi Teori Behavioristik dalam Pembelajaran Berbasis Teknologi Digital - M. Iqbal Ramadhiansyah; Agus Lestari (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The development of digital technology in the field of education has driven significant changes in the learning process. One theoretical approach that remains relevant in supporting technology-based learning is behaviorism theory, which emphasizes the relationship between stimulus and response as the foundation for the formation of learning behavior. This study uses a literature review method on ten selected articles to analyze the relevance of behaviorism theory in the digital learning ecosystem. The findings indicate that technologies such as interactive multimedia, e-learning applications, Computer Adaptive Instruction, and audio-visual media are capable of reinforcing behavioristic principles through structured stimuli, material repetition, and automatic feedback as a form of positive reinforcement. The use of technology has been proven to enhance motivation, focus, and learning outcomes of students. However, several challenges were identified, such as the risk of passive students, dependence on technological infrastructure, and the readiness of teachers to implement digital approaches. Overall, the literature review confirms that behaviorism theory remains relevant as a foundation for the design of technology-based learning, especially when combined with other approaches to create a more adaptive and effective learning process. Keywords: Behaviorism theory, educational technology, learning multimedia Abstrack Perkembangan teknologi digital dalam dunia pendidikan telah mendorong perubahan signifikan dalam proses pembelajaran. Salah satu pendekatan teoretis yang masih relevan dalam mendukung pembelajaran berbasis teknologi adalah teori behavioristik, yang menekankan hubungan antara stimulus dan respons sebagai dasar terbentuknya perilaku belajar. Penelitian ini menggunakan metode studi literatur terhadap sepuluh artikel terpilih untuk menganalisis relevansi teori behavioristik dalam ekosistem pembelajaran digital. Hasil kajian menunjukkan bahwa teknologi seperti multimedia interaktif, aplikasi e-learning, Computer Adaptive Instruction, serta media audio-visual mampu memperkuat prinsip-prinsip behavioristik melalui pemberian stimulus yang terstruktur, pengulangan materi, serta umpan balik otomatis sebagai bentuk penguatan positif. Penggunaan teknologi terbukti meningkatkan motivasi, fokus, dan hasil belajar peserta didik. Namun demikian, beberapa tantangan ditemukan, seperti risiko pasifnya siswa, ketergantungan pada infrastruktur teknologi, serta kesiapan guru dalam menerapkan pendekatan digital. Secara keseluruhan, temuan literatur mengonfirmasi bahwa teori behavioristik tetap relevan sebagai landasan perancangan pembelajaran berbasis teknologi digital, terutama ketika dikombinasikan dengan pendekatan lain untuk menghasilkan proses belajar yang lebih adaptif dan efektif. Kata Kunci: Teori behavioristik,teknologi pendidikan, multimedia pembelajaran